Solid waste cementing material as well as preparation and application methods thereof

Through the use of composite activators of silicate and phosphate and alkanolamine ester modifiers, the problems of low utilization rate and insufficient strength of solid waste cementitious materials are solved, and the efficient utilization and performance improvement of the materials are achieved, which is suitable for Rapid construction environment.

CN119330616APending Publication Date: 2025-01-21JSTI GRP CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411454053.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The utilization rate of existing solid waste gelling materials is low, insufficient strength, and complex production processes, resulting in waste of resources and environmental pollution.

Method used

Using composite initiators of silicate and phosphate and alkanolamine ester modifiers, by improving the ratio and preparation process of initiators and modifiers, the chemical reaction activity and microstructure of solid waste materials are enhanced, and the materials are improved. strength and durability.

Benefits of technology

It significantly improves the early strength and durability of solid waste cementitious materials, reduces production costs, simplifies the process, improves the density and anti-permeability of the material, and adapts to rapid construction environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005089961550000041
    Figure BDA0005089961550000041
  • Figure BDA0005089961550000051
    Figure BDA0005089961550000051
  • Figure BDA0005089961550000071
    Figure BDA0005089961550000071
Patent Text Reader

Abstract

The invention relates to the technical field of solid waste cementing materials, in particular to a solid waste cementing material and a preparation and application method thereof. The solid waste cementing material comprises the following components in parts by mass: 60-90 parts of a solid waste material; 5-30 parts of an exciting agent; 0.5 to 5 parts of an alcohol amine acid ester modifier; and 10-40 parts of water. By optimizing the reaction process of the excitant and the alcamine acid ester modifier, the solid waste cementing material can achieve high strength, durability and excellent construction performance. Phosphate and silicate in the exciting agent act together, so that the activity of the solid waste material is enhanced; and the alcohol amine acid ester modifier improves the fluidity and strength of the material through esterification reaction, and accelerates the reaction through the catalytic action of p-toluenesulfonic acid, so that the production efficiency is improved, and side reactions are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid waste gelling materials, and in particular to a solid waste gelling material and a preparation and application method thereof. Background Art

[0002] In the field of construction and civil engineering, the application of cementitious materials is of vital importance. With the improvement of environmental awareness and the increasing problem of resource shortage, the use of traditional cementitious materials (such as cement) faces challenges. The production process of cement consumes a large amount of natural resources and produces a large amount of greenhouse gases such as carbon dioxide. This process not only causes serious pollution to the environment, but also intensifies the consumption of resources. Therefore, there is an urgent need to find alternative materials to reduce dependence on traditional raw materials.

[0003] In the context of dual carbon, the research on new green and low-carbon cementitious materials has gradually become a hot topic. Solid waste materials (such as fly ash, slag and fly ash, etc.) are used to a certain extent in the preparation of cementitious materials, but the utilization rate of these materials in the existing technology is still low. Many solid waste materials have not been effectively recycled and utilized, resulting in resource waste and environmental pollution.

[0004] At present, many solid waste cementitious materials are often not comparable to traditional cement materials in terms of performance, especially in terms of strength, durability and anti-permeability. This limits the practical application of solid waste cementitious materials and fails to meet the demand for high-performance building materials. In addition, the existing preparation process of solid waste cementitious materials is usually complicated, requiring multiple steps and precise control of reaction conditions, resulting in increased production costs and increased difficulty in operation. This complexity not only affects production efficiency, but also reduces its market competitiveness.

[0005] The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a solid waste gelling material to solve the technical problems of low utilization rate of solid waste materials and low strength of solid waste gelling materials. In the production process, the emission of greenhouse gases such as carbon dioxide can be effectively reduced by adopting more environmentally friendly production technology, using alternative raw materials, reducing energy consumption or adopting carbon capture methods.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] A solid waste gelling material, comprising the following components in parts by weight:

[0009] Solid waste materials: 60-90 parts;

[0010] Stimulant: 5-30 parts;

[0011] Alcoholamine acid ester modifier: 0.5-5 parts;

[0012] Water: 10-40 parts.

[0013] Preferably, the solid waste material is one or more of fly ash, slag, fly ash, tailings and sludge.

[0014] Preferably, the activator is prepared as follows: 1-5 parts of phosphate solution are added to 5-20 parts of silicate solution to obtain a mixed solution, 0.5-10 parts of alkaline regulator and 5-10 parts of water are added to the mixed solution, magnetic stirring is performed for 5-10 minutes, and after the alkaline regulator is completely dissolved, the solution is sealed and allowed to stand for 20-30 hours to obtain the activator.

[0015] Among them, the alkaline regulator is used to dissolve the active ingredients in the solid waste material. In this process, the silicate solution and the phosphate solution work together to form active silicon and aluminum ions and promote the hydration reaction of the solid waste material; the introduction of phosphate helps to accelerate the reaction, form a more dense hydration product and form a network structure in the material, thereby enhancing the strength and durability of the material. The present invention enhances the chemical reaction activity of the solid waste material and improves the microstructure of the material through the composite excitation of phosphate and silicate.

[0016] Preferably, the silicate is one or more of metal cation solutions such as sodium silicate and calcium silicate; the phosphate is one or more of potassium phosphate and sodium phosphate; and the alkaline regulator is one or more of sodium hydroxide and calcium hydroxide. The good solubility of sodium silicate and sodium phosphate in water enables them to quickly release active ions, thereby improving the fluidity of the mixture and facilitating construction and molding. The present invention can effectively control the consistency of the gelling material by adjusting the ratio of silicate and phosphate to adapt it to different construction requirements. Sodium hydroxide and calcium hydroxide, as alkaline regulators, can not only adjust the pH value of the reaction system and enhance the alkaline environment of the system, but also improve the stability of the material in an acid-base environment and prevent corrosion and degradation of the material.

[0017] Preferably, the alcohol amine acid ester modifier is prepared as follows: 10-20 parts of alcohol amine compounds are put into a three-necked flask, 0.1-0.5 parts of a strong acid catalyst are added, the temperature is heated to 80-120°C, and 15-40 parts of anhydride solution are added dropwise, the addition is completed within 15-25 minutes, the reaction is continued for 4-8 hours, and after the reaction is completed, reduced pressure distillation is performed for 30-60 minutes to obtain the alcohol amine acid ester modifier.

[0018] In the reaction between alcoholamine compounds and acid anhydrides, the first reaction is esterification. Strong acid catalysts provide proton catalysis to promote the reaction between the carbonyl group (C=O) of the acid anhydride and the hydroxyl group (-OH) of the alcoholamine compound to generate alcoholamine acid ester products. During the process, the carboxyl group (-COOH) of the acid anhydride and the amine group (-NH2) and hydroxyl group (-OH) in the alcoholamine compound participate in the reaction at the same time to form stable alcoholamine acid esters. These esterification products not only increase the hydrophilicity and fluidity of the modifier, but also provide more reaction sites for the subsequent hydration reaction.

[0019] Preferably, the alcoholamine compound may be a compound carrying a hydroxyl group (-OH) and an amine group (-NH or -NR, R is a hydrocarbon group), which can undergo a cross-linking reaction with the active ingredients in the solid waste material to form a stronger chemical bond, thereby improving the strength and durability of the cementitious material. Such as one or more of triethanolamine, methylolamine, diethanolamine, isopropanolamine and aminomethyl propanol. Its molecular structure can produce a dispersing effect in an aqueous solution, prevent the precipitation of solid waste particles, and further ensure the stability and uniformity of the mixture.

[0020] Preferably, the acid anhydride can be an organic acid anhydride or an inorganic acid anhydride, specifically one or more of acetic anhydride, maleic anhydride, propionic anhydride, phthalic anhydride, succinic anhydride, and phosphoric anhydride. Acid anhydrides can react with hydroxyl groups and amine groups in alcohol amine compounds to form ester or amide compounds. They can increase the reactivity of the material, accelerate the curing process, and thus improve the early strength of the material.

[0021] Preferably, the strong acid catalyst is p-toluenesulfonic acid, which is used to promote the esterification reaction. p-Toluenesulfonic acid reduces the activation energy of the reaction by providing protons to the reaction system, so that the esterification reaction can be carried out at a relatively low temperature and in a shorter time. It attracts the carbon groups in the anhydride to combine with the hydroxyl groups in the alcohol amine, stabilizes the reaction intermediates, ensures the smooth progress of the reaction, and reduces the occurrence of side reactions.

[0022] The technical problem to be solved by the present invention is to provide a method for preparing a solid waste gelling material, and to improve the mechanical properties and durability of the solid waste gelling material by optimizing the ratio of an activator and a modifier and the preparation process.

[0023] In order to achieve the above object, the technical solution adopted by the present invention is:

[0024] A method for preparing a solid waste gelling material comprises the following steps:

[0025] Take 0.5-5 parts of alcohol amine acid ester modifier and 5-30 parts of activator, add to 30-50 parts of water, stir evenly, then add to 60-90 parts of solid waste materials, stir evenly to obtain solid waste gelling material.

[0026] The technical problem to be solved by the present invention is to provide an application method of solid waste gelling material, which has the same technical effect.

[0027] In order to achieve the above object, the technical solution adopted by the present invention is:

[0028] A method for applying solid waste cementitious materials, in which the solid waste cementitious materials replace all or part of cement and are used in the production of concrete, mortar and prefabricated components.

[0029] Specifically, mix the prepared cementitious material with the mineral material evenly, and then quickly pour it into the mold or construction site. Use a vibrator or manual tool to vibrate and beat the cementitious material to eliminate bubbles and ensure close contact between the material and the surface of the structure to avoid holes and cracks. After the cementitious material is poured, keep it moist for 7 to 28 days, depending on the project requirements. Common curing methods include spraying water or covering with a wet cloth to prevent the surface of the material from drying too quickly and causing cracks. The optimal curing temperature is between 15 and 25°C, and the humidity is kept above 70%. During the curing period, compressive strength tests can be carried out at different time points to ensure that the material meets the strength requirements of the design. After the test is qualified, subsequent construction or project acceptance can be carried out.

[0030] The beneficial effects of the present invention are:

[0031] The composite use of silicate and phosphate in the present invention enhances the excitation effect on the silicon and aluminum components in the solid waste material, accelerates the hydration reaction, and can significantly shorten the setting time of the material, making it more suitable for a fast construction environment. By introducing phosphate, the generation of CSH and phosphate-based products is promoted, so that the material has higher early strength and chemical stability. The generated hydration products are interwoven into a mesh structure, fill the pores of the material, reduce the porosity, improve the density and anti-permeability of the material, and then improve the compressive strength and durability of the material.

[0032] The alcohol amine acid ester modifier in the present invention can effectively reduce the internal friction between particles in the solid waste gel material system through physical adsorption, chemical reaction, plasticizing effect and regulation of hydration reaction, can improve the fluidity and construction performance of the material, effectively improve the workability of the material, and adapt to more complex construction environments. The esterification reaction product contains carboxyl and ester groups, and these functional groups can further react with hydrated calcium silicate to form a more dense and stable network structure, which significantly improves the later strength and durability of the material. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0035] In the examples of the present invention, the sources of commercially available materials are as follows:

[0036]

[0037]

[0038] In order to characterize the performance of solid waste cementitious materials, this patent refers to GB / T 17671-2021 "Test Method for Cement Mortar Strength" (ISO method) to carry out mortar strength test. Ensure that the laboratory temperature is maintained at 20±2℃ and the relative humidity is not less than 50%. At the same time, the temperature of the molded specimen curing box should be maintained at 20±1℃, and the relative humidity should not be less than 90%; the water temperature of the specimen curing pool should also be maintained at 20±1℃. The mass ratio of solid waste material to standard sand is 1:3, and the water-cement ratio is 0.5.

[0039] Example 1

[0040] (1) Take 15 parts of triethanolamine in a three-necked flask, add 0.3 parts of dodecylbenzenesulfonic acid, heat the temperature to 110°C, and dropwise add 30 parts of maleic anhydride solution. The dropwise addition is completed within 25 minutes, and the reaction is continued for 8 hours. After the reaction is completed, the mixture is distilled under reduced pressure for 60 minutes to obtain an alcohol amine acid ester modifier.

[0041] (2) Take 5 parts of sodium hydroxide and 10 parts of water and add them to a mixed solution of 20 parts of sodium silicate solution and 2 parts of sodium phosphate solution, stir magnetically for 10 minutes, and after the alkaline regulator is completely dissolved, seal and let stand for 24 hours to obtain an activator.

[0042] (3) Add 3 parts of alcohol amine acid ester modifier and 25 parts of activator to 40 parts of water and mix evenly. After stirring evenly, add to 80 parts of slag and stir at a low speed for 30 seconds according to the specification. At the beginning of the second 30 seconds, evenly add 1350g of sand, and then adjust to high speed stirring for 30 seconds. Stop stirring for 90 seconds. Within 15 seconds after the start of stopping stirring, quickly pour the prepared mixed material into the mold, use a vibrator or manual tool to vibrate and beat the cementitious material to eliminate bubbles, and ensure that the material is in close contact with the surface of the structure to avoid holes and cracks; after pouring, cover with a wet cloth to keep it moist and maintain it, so as to obtain a solid waste material mortar specimen, the curing time is 7 days, the curing temperature is between 25℃, and the humidity is kept above 70%; after curing for 7 days, test its compressive and flexural strength. Among them, 80 parts of slag are 450g, and the remaining parts are converted according to proportion.

[0043] Example 2

[0044] (1) Take 12 parts of methyl alcohol amine in a three-necked flask, add 0.2 parts of p-toluenesulfonic acid, heat the temperature to 110°C, and dropwise add 25 parts of maleic anhydride solution. The dropwise addition is completed within 20 minutes, and the reaction is continued for 6 hours. After the reaction is completed, the reduced pressure distillation is carried out for 40 minutes to obtain an alcohol amine acid ester modifier.

[0045] (2) Take 3 parts of sodium hydroxide and 7 parts of water and add them to a mixed solution of 15 parts of sodium silicate solution and 1 part of sodium phosphate solution, stir magnetically for 10 minutes, and after the alkaline regulator is completely dissolved, seal and let stand for 18 hours to obtain an activator.

[0046] (3) Add 4 parts of alcohol amine acid ester modifier and 20 parts of activator to 35 parts of water and mix evenly. After stirring evenly, add to 70 parts of fly ash and stir at a low speed for 30 seconds according to the specification. At the beginning of the second 30 seconds, evenly add 1350g of sand, and then adjust to high speed stirring for 30 seconds. Stop stirring for 90 seconds. Within 15 seconds after the start of stopping stirring, quickly pour the prepared mixed material into the mold, use a vibrator or manual tool to vibrate and beat the cementitious material to eliminate bubbles, and ensure that the material is in close contact with the surface of the structure to avoid holes and cracks; after pouring, cover with a wet cloth to keep it moist and maintain it, so as to obtain a solid waste material mortar specimen, the curing time is 7 days, the curing temperature is between 25℃, and the humidity is kept above 70%; after curing for 7 days, test its compressive and flexural strength. Among them, 80 parts of fly ash are 450g, and the remaining parts are converted according to proportion.

[0047] Example 3

[0048] (1) Take 20 parts of triethanolamine in a three-necked flask, add 0.5 parts of p-toluenesulfonic acid, heat the temperature to 120°C, and dropwise add 40 parts of acetic anhydride solution. The dropwise addition is completed within 25 minutes, and the reaction is continued for 8 hours. After the reaction is completed, the mixture is distilled under reduced pressure for 60 minutes to obtain an alcohol amine acid ester modifier.

[0049] (2) Take 7 parts of sodium hydroxide and 10 parts of water and add them to a mixed solution of 20 parts of sodium silicate solution and 1 part of sodium phosphate solution, stir magnetically for 10 minutes, and after the alkaline regulator is completely dissolved, seal and let stand for 30 hours to obtain an activator.

[0050] (3) Add 5 parts of alcohol amine acid ester modifier and 30 parts of activator to 40 parts of water and mix evenly. After stirring evenly, add to 80 parts of fly ash and stir at a low speed for 30 seconds according to the specification. At the beginning of the second 30 seconds, evenly add 1350g of sand, and then adjust to high speed stirring for 30 seconds. Stop stirring for 90 seconds. Within 15 seconds after the start of stopping stirring, quickly pour the prepared mixed material into the mold, use a vibrator or manual tool to vibrate and beat the cementitious material to eliminate bubbles, and ensure that the material is in close contact with the surface of the structure to avoid holes and cracks; after pouring, cover with a wet cloth to keep it moist for 7 days, the curing temperature is between 25°C, and the humidity is kept above 70%; the solid waste material mortar specimen is obtained, and its compressive and flexural strength is tested after curing for 7 days. Among them, 80 parts of fly ash are 450g, and the remaining parts are converted according to proportion.

[0051] Comparative Example 1

[0052] The comparative example is the strength of cement mortar. The specific operations include the following:

[0053] Add 225g of water to the mixer, then add 450g of cement, stir at a low speed for 30s according to the specification, and evenly add 1350g of sand at the beginning of the second 30s, and then adjust to high-speed stirring for 30s. Stop stirring for 90s, and within 15s of the start of stopping stirring, quickly pour the prepared mixed material into the mold, use a vibrator or manual tool to vibrate and beat the cementitious material to eliminate bubbles, and ensure that the material is in close contact with the surface of the structure to avoid holes and cracks; after pouring, cover with a wet cloth to keep it moist for 7 days, the curing temperature is between 25℃, and the humidity is kept above 70%; the solid waste material mortar specimen is obtained, and its compressive and flexural strength is tested after curing for 7 days.

[0054] Performance Verification

[0055] The compressive and flexural properties of the above mortar specimens were tested, and the results are shown in Table 1.

[0056] Table 1 Strength index of mortar specimens

[0057]

[0058] In summary, the present invention provides a preparation process of a solid waste cementitious material, thereby effectively utilizing the solid waste material, improving the mechanical properties of the solid waste cementitious material, and can fully or partially replace cement.

[0059] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A solid waste gelling material, characterized in that: The composition comprises the following components in parts by weight: Solid waste materials: 60-90 parts; Stimulant: 5-30 parts; Alcoholamine acid ester modifier: 0.5-5 parts; Water: 10-40 parts.

2. A solid waste gelling material according to claim 1, characterized in that: The solid waste material is one or more of fly ash, slag, fly ash, tailings and sludge.

3. The solid waste gelling material according to claim 1, characterized in that: The activator is prepared as follows: 1-5 parts of phosphate solution are added to 5-20 parts of silicate solution to prepare a mixed solution, 0.5-10 parts of alkaline regulator and 5-10 parts of water are added to the mixed solution, magnetic stirring is performed for 5-10 minutes, and after the alkaline regulator is completely dissolved, the mixture is sealed and allowed to stand for 20-30 hours to obtain the activator.

4. A solid waste gelling material according to claim 3, characterized in that: The silicate is one or more of sodium silicate and calcium silicate; the phosphate is one or more of potassium phosphate and sodium phosphate; the alkaline regulator is one or more of sodium hydroxide and calcium hydroxide.

5. The solid waste gelling material according to claim 1, characterized in that: The alcoholamine acid ester modifier is prepared as follows: 10-20 parts of alcoholamine compounds are put into a three-necked flask, 0.1-0.5 parts of a strong acid catalyst are added, the temperature is heated to 80-120° C., and 15-40 parts of anhydride solution are added dropwise, the addition is completed within 15-25 minutes, the reaction is continued for 4-8 hours, and after the reaction is completed, reduced pressure distillation is performed for 30-60 minutes to obtain the alcoholamine acid ester modifier.

6. The solid waste gelling material according to claim 5, characterized in that: The alcoholamine compound is one or more of triethanolamine, methylolamine, diethanolamine, isopropanolamine and aminomethylpropanol.

7. The solid waste gelling material according to claim 5, characterized in that: The acid anhydride is one or more of acetic anhydride, maleic anhydride, propionic anhydride, phthalic anhydride, succinic anhydride and phosphoric anhydride.

8. The solid waste gelling material according to claim 5, characterized in that: The strong acid catalyst is p-toluenesulfonic acid.

9. The method for preparing a solid waste gelling material according to any one of claims 1 to 8, characterized in that: The steps are as follows: Take 0.5-5 parts of alcohol amine acid ester modifier and 5-30 parts of activator, add to 30-50 parts of water, stir evenly, then add to 60-90 parts of solid waste materials, stir evenly to obtain solid waste gelling material.

10. The method for applying the solid waste gelling material according to any one of claims 1 to 8, characterized in that: The solid waste cementitious material is used to replace all or part of the cement in the production of concrete, mortar and prefabricated components.

Citation Information

Cited By

  • Geopolymer concrete dry blend as well as preparation method and application thereof

    CN120965194A